2021
DOI: 10.3390/diagnostics11020150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Small Dosimeters Used for Measurement of Eye Lens Dose for Medical Staff during Fluoroscopic Examination

Abstract: This study aimed to evaluate the property of small dosimeters used for measuring eye lens doses for medical staff during fluoroscopic examination. Dose linearity, energy dependence, and directional dependence of scattered X-rays were evaluated for small radiophotoluminescence glass dosimeters (RPLDs), those with a tin filter (Sn-RPLDs), and small optically stimulated luminescence dosimeters (OSLDs). These dosimeters were pasted on radioprotective glasses, and accumulated air kerma was obtained after irradiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The response of the nanoDot in terms of dose linearity was linearly proportional to the exposure in the studies by Al-Senan and Hatab [11] and Matsubara et al [12]. Additionally, the present study revealed that the nanoDot had excellent linearity (R 2 = 1.00) with the air kerma up to 21.4 mGy.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The response of the nanoDot in terms of dose linearity was linearly proportional to the exposure in the studies by Al-Senan and Hatab [11] and Matsubara et al [12]. Additionally, the present study revealed that the nanoDot had excellent linearity (R 2 = 1.00) with the air kerma up to 21.4 mGy.…”
Section: Discussionsupporting
confidence: 73%
“…However, studies using the Vision badge were limited to those for staff at the Fukushima Daiichi Nuclear Power Plant in Japan [9] and the nuclear medicine department [10]. Although basic characteristics of small optically stimulated luminescence (OSL) dosimeters (nanoDot; Landauer, Glenwood, IL, USA) has been reported [11,12], there are no papers describing their basic characteristics for Vision badge, and no manufacturer data has been disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Although they need to learn about disaster exposure and counseling, they may become personnel who can be responsible for responding to residents' concerns about disaster exposure in the event of a radiation disaster. They also play an important role in occupational radiation protection in facilities with medical radiation equipment [27][28][29][30][31][32][33][34][35][36][37][38]. Radiation safety measures are necessary for medical radiologic technologists, who are familiar with radiation risks and protection [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…OSLDs' potential in medical dosimetry was recognized due to their excellent reproducibility, negligible angular dependence, and small size suitable for point measurements. OSLDs are increasingly used for the evaluation of radiation doses in diagnostic radiology [20,21], such as eye lens doses of medical staff during fluoroscopic examination [22] and occupational radiation dose during fluoroscopy-guided interventional procedures [23].…”
Section: Introductionmentioning
confidence: 99%